Chemistry of biologically potent natural products and synthetic compounds - Ul-Islam, Shahid; Banday, Javid Ahmad (Emerging trends in medicinal and pharmaceutical chemistry., 2021)
"In view of their promising biological and pharmaceutical activities, natural product inspired and heterocyclic compounds have recently gained a reputation in the field of medicinal chemistry. Over the past decades, intensive research efforts have been ongoing to understand the synthesis, biochemistry and engineering involved in their preparation and action mechanisms. Several novel natural product derivatives, heterocyclic and other synthetic compounds, have been reported to have shown interesting biological activities including anticancer, antimicrobial, anti-inflammatory, anti-glycemic, anti-allergy and antiviral etc. Chemistry of Biologically Potent Natural Products and Synthetic Compounds provides up-to-date information on new developments and most recent medicinal applications of the natural products and derivatives, as well as the chemistry and synthesis of heterocyclic and other related compounds"--